1999
DOI: 10.1002/14651858.cd000346
|View full text |Cite|
|
Sign up to set email alerts
|

Gonadotrophin-releasing hormone analogues for pain associated with endometriosis

Abstract: There is little or no difference in the effectiveness of GnRHas in comparison with other medical treatments for endometriosis. GnRHas do appear to be an effective treatment. Differences that do exist relate to side effect profiles. Side effects of GnRHas can be ameliorated by the addition of addback therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
57
0
6

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(63 citation statements)
references
References 54 publications
0
57
0
6
Order By: Relevance
“…[7][8][9] Surgery for rectovaginal endometriosis can be complex and challenging and often involves a multidisciplinary team (MDT). The choice of surgery will depend to some extent on the reproductive plans of the women as well as the surgical skill available.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] Surgery for rectovaginal endometriosis can be complex and challenging and often involves a multidisciplinary team (MDT). The choice of surgery will depend to some extent on the reproductive plans of the women as well as the surgical skill available.…”
Section: Introductionmentioning
confidence: 99%
“…For empiric medical therapy, OCPs and medroxyprogesterone acetate have apparent therapeutic equivalence and should be used as first-line therapies. [24][25][26] Many sources support the empiric use of GnRHas for treatment of the pain associated with endometriosis; 27 however, a systematic review found them to be no more effective than OCPs or progestogens 24 (online Table A). Furthermore, GnRHas can have hypoestrogenic side effects.…”
Section: Diagnostic Strategymentioning
confidence: 99%
“…28 These side effects may be alleviated somewhat with add-back therapy (i.e., replacement of hormones blocked by the action of GnRHas) without diminishing the effect of the GnRHa; however, the optimal method of add-back therapy has not been established. 27 One small study found the levonorgestrelreleasing intrauterine system (Mirena) to be effective in postoperative treatment for dysmenorrhea. 29 www …”
Section: Diagnostic Strategymentioning
confidence: 99%
“…The other problem associated with a 6-month course of GnRH-a is a reduction in vertebral bone mineral density (BMD) of approximately 3-4%. This concern has therefore limited its use to a 6-month duration [8,9]. In a multicentre randomised doubleblinded trial using a 12-month course of GnRH alone, women experienced a BMD loss in the lumber spine of 3.2% at 6 months and 6.3% at 12 months and com-plained of hot flashes, which were dramatically suppressed in the add-back HRT groups, whereas women receiving add-back HRT for 12 months had a significantly negligible (<1%) BMD loss [14].…”
Section: Gnrh-a Therapymentioning
confidence: 99%
“…Both have been shown to decrease symptoms when compared with placebo [6,7]. A large Cochrane metaanalysis of 26 randomised controlled trials confirmed GnRH-a to be effective in relieving pain [8,9]. However, long-term follow-up studies show a high recurrence rate following medical treatment [10,11].…”
Section: Introductionmentioning
confidence: 99%